Walter Scheidel, Escape from Rome. The Failure of Empire and the Road to Prosperity - Ward-Perkins, Bryan (Journal of Greek Archaeology, 2021)
This is a long book with a big theory: that innate features in Europe’s geography and culture made it peculiarly empire-proof after the collapse of Rome, and that it is the failure of any empire to control Europe that best explains the exceptional technological, scientific and economic development which gave us the world we have today, in which the majority of us are ‘so much richer, healthier and better educated than our ancestors used to be’ (p. 1). The principal driver of this change is for Scheidel the persistent polycentrism in Europe after Rome, and the consequent thriving of competition, not only between numerous independent states but also within states, between different groups competing for wealth and influence – merchants, lords, bishops and kings.